Various Types of Acids on Pretreatment of Corn Stover for Enhancing Biogas Yield - Lukhi Mulia Shitophyta; Zahra Lintang Cahyaningtyas; Nurul Aulia Syifa; Firda Mahira Alfiata Chusna (JTERA (Jurnal Teknologi Rekayasa), 2022)
Biogas production from lignocellulosic biomass has gained attention in the development of renewable fuels. Corn stover belongs to lignocellulosic biomass. Pretreatment is needed to help the digestion of biomass due to its lignocellulosic recalcitrance. This study aims to compare the different types of acids for enhancing biogas production. The experiment was carried out in a 1 L batch digester at room temperature with different acids of HCl, H2SO4, and C2H2O4 at concentrations of 0%, 5%, 10%, and 15%. The acids pretreatment was performed for 24 hr. Results show that pretreatment of C2H2O4 has a positive impact on increasing biogas yield. The highest cumulative yield of 580.8 mL/gVS is obtained at 15% C2H2O4. The increase in acid concentrations decreases the initial pH value. The pH value below 6 reduces biogas yield.